Development of Project-Based Learning (PjBL)-Based Interactive Teaching Materials for Response Text Learning in Class VII.4 at SMPN 10 Pekanbaru - Muliana; Asnawi (Lembaga Bale Literasi, 2026)
This study aims to develop interactive teaching materials based on Project Based Learning (PjBL) for response text learning in seventh-grade students of SMP Negeri 10 Pekanbaru. The study was motivated by students’ low ability in writing response texts, the limited use of interactive media in learning activities, and the predominance of conventional teaching materials that are less engaging. This research employed the Research and Development (R&D) method using the ADDIE development model, which was limited to the stages of analysis, design, and development. The research subjects consisted of Indonesian language teachers and seventh-grade students of SMP Negeri 10 Pekanbaru in the 2025/2026 academic year who were involved in the needs analysis stage. The research instruments included interview guidelines, needs analysis questionnaires, and expert validation sheets. The product developed was an interactive e-module based on Project Based Learning (PjBL) using digital media that can be accessed through smartphones and laptops. The results indicated that the developed teaching material achieved a highly valid category based on expert validation. Language expert validation obtained a score of 97.5% (highly valid), material expert validation obtained 97.5% (highly valid), media expert validation obtained 85% (valid), and technology-content expert validation obtained 80% (valid). Based on the combined validity calculation, the overall validity score reached 90%, indicating that the e-module is highly valid and suitable for use as a learning resource. Furthermore, the needs analysis revealed that students preferred interactive digital teaching materials with simple language, attractive visuals, project-based activities, and practical writing exercises. Therefore, it can be concluded that the interactive teaching material based on Project Based Learning (PjBL) for response text learning was successfully developed according to students’ needs and is appropriate for use in Indonesian language learning at the junior high school level.